Pengaruh Penerapan Model Pembelajaran KooperatifTipe Formulate Share Listen And Create (FSLC) TerhadapKemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMP Negeri 1 Tigo Nagari - SILVINA AMIR (Departemen Matematika, 2020)
Mathematical communication skill is one of the abilities that must be managed and owned by each student.Based on the results of observations and tests given, students' mathematical communication skill are lacking. One contributing factor is learning that has not been fully able to facilitate students to be able to develop their mathematical communication skills. The learning model that can facilitate students to improve their mathematical communication skills is cooperative learningmodels type Formulate, Share, Listen, And Create (FSLC). The purpose of this study was to determine and describe whether the mathematical communication skills of students who learn using cooperative learning models type FSLC is better than the mathematical communication skills of students who learn by using direct learning models in class VIII of SMP Negeri 1 Tigo Nagari. Based on the results of data analysis, it was concluded that mathematical communication skills of students who study with cooperative learning models type FSLC is better than students who learn with direct learning models in class VIII of SMP Negeri 1 Tigo Nagari. Keyword – Mathematical communication skill, CooperativeLearning, Formulate Share Listen and Create, Direct Learning